Structural-Functional Analysis of Contract Categories - Xo‘jabekova Zarnigor; Normo'minov Sherzod To'ychiyevich (European Science Publishing, 2023)
This article provides detailed information about the form and role of the case categories in the Uzbek language. Each category of case is addressed separately, and an attempt is made to justify the opinions with various examples of their marked or unmarked use. Comments are made regarding the historical forms of case and today's options as well. Attention has been paid to conjunctions are considered an abstract grammatical category when they are taken separately from the word to which they are added and aspects such as the fact that its meaning cannot be imagined separately from the meaning of the word to which it is added.
Keywords: case, lexicon, variation, category, genitive, input, output.